Breeding cassava for resistance to bacterial blight - Hahn, S.K. (1978)
It is noted that cassava bacterial blight (CBB) has been reported in several African countries and that heavy infection with CBB can lead to total crop failure as most local varieties are very susceptible. The best control method is through varietal resistance. IITA has made progress in breeding for resistance to both CBB and cassava mosaic disease (CMD) incorporating simultaneously other desirable agronomic qualities. The cassava breeding work at IITA since 1972 is then discussed covering tests on a total of 583 cassava families from CIAT, East Africa and IITA for sources of high resistance to CBB, further tests on 748 IITA clones for CBB resistance in a given ecological setting of high rainfall, sandy and acid soil from which the cultivar 58308 emerged highly resistant. Other aspects of the breeding work treated are conditions affecting varietal selection, namely: genetic mechanism resistance: stability of resistance to CBB over time and in different areas in Africa; high heritability; genetic correlation between resistance to CBB and CMD; correlation of CBB resistance with other characteristics such as tuber yield and leaf defoliation; and finally some factors affecting CBB field scores which are time of planting, age of plant and time of observation. It is noted that the sources of high resistance to CBB identified have been quickly and successfully incorporated into promising cassava clones.